Development of Innovative Packaging Design for Madura Cassava Chips to Improve Product Competitiveness - Buyung Adi Dharma; Hermawan, Agus; Suharsono, Naswan (Economics and Business Journal (ECBIS), 2023)
This research aims to develop the design and packaging of Madurese Cassava Chips products at Mrs X's UMKM. The research method used is a research and development model using the ADDIE model. The sample used in this study totalled 55 respondents. The data collection instrument used is a questionnaire sheet in the form of a google form. There are validation results from design experts and business practitioner experts, which are very feasible. The product was then tested on 55 respondents who were divided into two groups, namely 31 respondents were consumers of Madura Cassava Chips products who had purchased the product before development with the results being quite feasible to use and 24 respondents were consumers of Madura Cassava Chips products who had purchased the product after development with the results being very feasible to use. From the results of the pretest and posttest, it was found that there were differences in product packaging design on the competitiveness of Mrs X's MSMEs before and after developing the Madura Cassava Chips product packaging design. Based on the results that have been obtained, the development of the Madura Cassava Chips product design and packaging is very feasible to use